Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
c) 1 1/4 * 6 - 3 : 1 1/5=5/4*6- 3:6/5=15/2 -3*5/6=15/2 -5/2=10/2=5
e) 2 1/5 - 1 1/6 : 2 1/3 =2 1/5 -7/6:7/3=2 1/5 -7/6*3/7=2 1/5- 2=1/5
f) [( 3/8 + 1/6) : 3 1/4] - (1/3)³=[(9/24+4/24):13/4]-1/27=(13/24:13/4) -1/27=13/24*4/13 -1/27=1/6 -1/27= 27/162 -6/162=21/162=7/54
g) 5/8 : 1 2/3 + 1 4/5 * 5/6 - 5/9 * (1 3/4 - 2/5) + 1 5/6=5/8:5/3+9/5*5/6 -5/9*(1 15/20-8/20)+1 5/6=5/8*3/5 +3/2 -5/9* 1 7/20 +1 5/6=3/8+1 1/2-5/9*27/20=3/8+1 4/8 -3/4=1 7/8 -6/8=1 1/8
h) 1 1/3 *1 1/4 - 1 1/2 : 1 1/5 + 1 1/8 : (1 1/8 - 3/4) + 1 5/6=4/3*5/4 -3/2:6/5 +9/8 :(1 1/8 -6/8)+1 5/6=5/3 -3/2*5/6 +9/8:(9/8-3/8)+1 5/6=1 2/3- 5/4+9/8:6/8 +1 5/6=1 2/3 -1 1/4+ 9/8*8/6 +1 5/6=1 8/12 -1 3/12+3/2 +1 10/12= 5/12+1 1/2+1 10/12= 5/12+1 6/12+1 10/12=2 21/12=3 9/12=3 3/4
Odpowiedź:
[tex]c)\ \ 1\frac{1}{4}\cdot6-3:1\frac{1}{5}=\frac{5}{\not4_{2}}\cdot\not6^3-3:\frac{6}{5}=\frac{5}{2}\cdot3-\not3^1\cdot\frac{5}{\not6_{2}}=\frac{15}{2}-\frac{5}{2}=\frac{10}{2}=5\\\\\\e)\ \ 2\frac{1}{5}-1\frac{1}{6}:2\frac{1}{3}=2\frac{1}{5}-\frac{7}{6}:\frac{7}{3}=2\frac{1}{5}-\frac{\not7^1}{\not6_{2}}\cdot\frac{\not3^1}{\not7_{1}}=2\frac{1}{5}-\frac{1}{2}=2\frac{2}{10}-\frac{5}{10}=1\frac{12}{10}-\frac{5}{10}=1\frac{7}{10}[/tex]
[tex]f)\ \ [(\frac{3}{8}+\frac{1}{6}):3\frac{1}{4}]-(\frac{1}{3})^3=[(\frac{9}{24}+\frac{4}{24}):\frac{13}{4}]-\frac{1}{27}=(\frac{\not13^1}{\not24_{6}}\cdot\frac{\not4^1}{\not13_{1}})-\frac{1}{27}=\frac{1}{6}-\frac{1}{27}=\\\\=\frac{9}{54}-\frac{2}{54}=\frac{7}{54}[/tex]
[tex]g)\ \ \frac{5}{8}:1\frac{2}{3}+1\frac{4}{5}\cdot\frac{5}{6}-\frac{5}{9}\cdot(1\frac{3}{4}-\frac{2}{5})+1\frac{5}{6}=\frac{5}{8}:\frac{5}{3}+\frac{\not9^3}{\not5_{1}}\cdot\frac{\not5^1}{\not6_{2}}-\frac{5}{9}\cdot(1\frac{15}{20}-\frac{8}{20})+1\frac{5}{6}=\\\\=\frac{\not5}{8}\cdot\frac{3}{\not5}+\frac{3}{2}-\frac{5}{9}\cdot1\frac{7}{20}+1\frac{5}{6}=\frac{3}{8}+\frac{3}{2}-\frac{\not5^1}{\not9_{1}}\cdot\frac{\not27^3}{\not20_{4}}+1\frac{5}{6}=[/tex][tex]=\frac{3}{8}+1\frac{1}{2}-\frac{3}{4}+1\frac{5}{6}=\frac{9}{24}+1\frac{12}{24}-\frac{18}{24}+1\frac{20}{24}=1\frac{21}{24}+1\frac{20}{24}-\frac{18}{24}=2\frac{41}{24}-\frac{18}{24}=2\frac{23}{24}[/tex]
[tex]h)\ \ 1\frac{1}{3}\cdot1\frac{1}{4}-1\frac{1}{2}:1\frac{1}{5}+1\frac{1}{8}:(1\frac{1}{8}-\frac{3}{4})+1\frac{5}{6}=\frac{\not4}{3}\cdot\frac{5}{\not4}-\frac{3}{2}:\frac{6}{5}+\frac{9}{8}:(\frac{9}{8}-\frac{3}{4})+1\frac{5}{6}=\\\\=\frac{5}{3}-\frac{\not3^1}{2}\cdot\frac{5}{\not6_{2}}+\frac{9}{8}:(\frac{9}{8}-\frac{6}{8})+1\frac{5}{6}=\frac{5}{3}-\frac{5}{4}+\frac{9}{8}:\frac{3}{8}+1\frac{5}{6}=[/tex][tex]=1\frac{2}{3}-1\frac{1}{4}+\frac{\not9^3}{\not8_{1}}\cdot\frac{\not8^1}{\not3_{1}}+1\frac{5}{6}=1\frac{2}{3}-1\frac{1}{4}+3+1\frac{5}{6}=1\frac{8}{12}-1\frac{3}{12}+3+1\frac{10}{12}=\frac{5}{12}+3+1\frac{10}{12}=\\\\=1\frac{15}{12}+3=2\frac{3}{12}+3=2\frac{1}{4}+3=5\frac{1}{4}[/tex]